THE TEACHER'S ROLE IN INTERNALIZING LOCAL WISDOM VALUES AT SMA PGRI KUPANG - Imelda Sari Inda Momay; Budiyanto Tukang (SocioEdu: Sociological Education, 2023)
This study aims to determine the role of teachers in SMA PGRI Kupang and to find out how teachers internalize local wisdom values in SMA PGRI Kupang. The type of research used for this research is qualitative to understand in depth the role of the teacher in internalizing local wisdom values at SMA PGRI Kupang. Data collection techniques used are observation, interviews and documentation. The results of this study indicate that the teacher's role at SMA PGRI Kupang is that the teacher internalizes the value of local wisdom so that students continue to preserve local wisdom that has existed for a long time from religious values that require students to pray before carrying out learning activities with the aim of students remaining for teachings of their respective religions. Second, the value of Gotong Royong with the aim of creating cohesiveness, fostering an attitude of helping each other and strengthening a sense of brotherhood. Third, cultural and artistic values that require students to comply with the rules in SMA PGRI Kupang and continue to practice positive habits such as 3S culture (smile, greet, greet), use of school uniforms according to the rules and recommendations for maintaining 5K (cleanliness, security, order, beauty and kinship).